Relapsing polychondritis: state of the art on clinical practice guidelines. (18th October 2018) - Rednic, Simona; Damian, Laura; Talarico, Rosaria; Scirè, Carlo Alberto; Tobias, Alexander; Costedoat-Chalumeau, Nathalie; Launay, David; Mathian, Alexis; Matthews, Lisa; Ponte, Cristina; Toniati, Paola; Bombardieri, Stefano; et al.
Abstract : Due to the rarity of relapsing polychondritis (RP), many unmet needs remain in the management of RP. Here, we present a systematic review of clinical practice guidelines (CPGs) published for RP, as well as a list of the most striking unmet needs for this rare disease. We carried out a systematic search in PubMed and Embase based on controlled terms (medical subject headings and Emtree) and keywords of the disease and publication type (CPGs). The systematic literature review identified 20 citations, among which no CPGs could be identified. We identified 11 main areas with unmet needs in the field of RP: the diagnosis strategy for RP; the therapeutic management of RP; the management of pregnancy in RP; the management of the disease in specific age groups (for instance in paediatric-onset RP); the evaluation of adherence to treatment; the follow-up of patients with RP, including the frequency of screening for the potential complications and the optimal imaging tools for each involved region; perioperative and anaesthetic management (due to tracheal involvement); risk of neoplasms in RP, including haematological malignancies; the prevention and management of infections; tools for assessment of disease activity and damage; and patient-reported outcomes and quality of life indicators. Patients and physicians should work together within the frame of the ReCONNET network to derive valuable evidence for obtaining literature-informed CPGs.